Dynamically sabotage-proof tournaments - Junichiro Ishida (Osaka University, Institute of Social and Economic Research (ISER), 2012)
This paper explores the consequences of sabotage for the design of incentive contracts. The possibility of sabotage gives rise to a dynamic concern, similar to the Ratchet effect, which distorts the agents' incentives. We first show that the mere possibility of sabotage may make it impossible to implement the first-best effort, and then offer two distinct incentive schemes, fast track and late selection, to circumvent this problem. The present model offers a mechanism through which these two schemes arise in a unified framework.
Keywords: J41; M12; 330; Sabotage; Tournament; Fast track; Late selection; Arbeitsvertrag; Anreizvertrag; Arbeitsethik; Theorie